Heart rate variability : a tool to explore autonomic nervous system activity in health and disease - Vigo, Daniel Eduardo (2019)
Fil: Vigo, Daniel Eduardo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina